Patients With Fibrotic Interstitial Lung Disease Receive Supportive and Palliative Care Just Prior to Death. (February 2021) - Smallwood, Natasha; Mann, Jennifer; Guo, Hui; Goh, Nicole
Background: Fibrotic interstitial lung diseases (f-ILDs) are often progressive and incurable. As patients experience significant symptoms and have a poor prognosis, early palliative care referral is recommended. Objective: To examine the care delivered to patients with f-ILD during the terminal hospital admission and the past 2 years of life. Methods: A retrospective audit was performed for consecutive patients who died from f-ILD at 2 Australian teaching hospitals between January 1, 2012, and December 31, 2016. Results: Of 67 patients, 44 (66%) had idiopathic pulmonary fibrosis. Median age was 78 years. Median respiratory function: forced expiratory volume in 1 second 69.0% predicted (interquartile range [IQR]: 58.0%-77.0%), forced vital capacity 64.0% predicted (IQR = 46.8%-74.3%), and diffusing capacity of carbon monoxide 36.0% predicted (IQR = 31.0%-44.0%). In the 2 years prior to the terminal admission, 38 (57%) patients reported severe breathlessness and 17 (25%) used opioids for symptom relief. Twenty-four (36%) patients received specialist palliative care (SPC) and 11 (16%) completed advance care planning. During the terminal admission, 10 (15%) patients were admitted directly under SPC. A further 33 (49%) patients were referred to SPC, on average 1 day prior to death. Sixty-three (94%) patients received opioids and 49 (73%) received benzodiazepines for symptom management. Median starting and final opioid doses were 10 and 23 mg oral morphine equivalent/24 hours, respectively. Opioids were commenced on average 2 (IQR 1-3) days prior to death. Conclusions: Although most patients were identified as actively dying in the final admission, referral to SPC and use of palliative medications occurred late. Additionally, few patients accessed symptom palliation earlier in their illness.